Population Characteristics of Unexploited Beaver and Muskrat Populations - Zeckmeister, Michael T. (University of Wisconsin-Stevens Point, College of Natural Resources, 1985)
A trapline system for beaver (Castor canadensis) and muskrat (Ondatra zibethicus) occurred on Sandhill Wildlife Area during 1981, 1982, and 1983 to harvest populations unexploited for at least 19 years. We censused 48 beaver colonies (1.30/km^2) in 1981, 38 (1.02/km^2) in 1982, and 18 (0.49/km^2) in 1983. A winter harvest of 3.9 beaver/colony in 1981 rresulted in a 21% decline in active colonies; subsequent harvest of 3.2 beaver/colony in 1982 caused a 58% decline. In 1981 and 1982, 89% of the beaver harvest was achieved during the first 16 days of the season and involved 64% of the trapping effort. Lack of exploitation may have delayed sexual maturation and dispersal and increased the number of non-.breeding adults. In 1981, 35% of the females (N=51) had placental scars, fewer (P>0.05) than the 80% (N=25) found in 1982. Breeding females averaged 3.1 placental scars in 1981 (N=56) and 3.6 in 1982 (N=72). Yearlings reproduced after 1 year of harvest when about 79% of the available colony sites were occupied. Despite an initial increase in reproductive effort after 1 season of harvest, the population was reduced after the 2nd harvest, apparently due to the effective system of harvest. Muskrat harvest and number of trapnights declined (P>0.05) after 1981. Sex ratios of adults and juveniles favored males (P<0.05) all years. The harvest of 245 young/100 adults in 1981 was different (P>0.05) from the 180/100 adults in 1983, but not different from the 198/100 adults in 1982. Placental scars averaged 9.5/adult female (N=166) for the 3 years. Marsh fertility appears to influence sex-specific mortality and limit reproductive success of muskrats on Sandhill.
Effects of Trapping on Beaver Colony Density, Structure, and Reproduction
Structure of an Unharvested Muskrat Population in an Infertile Wetland